EVALUATION OF TOTAL BACTERIA IN SMALL INTESTINE ILEUM OF THE INDONESIAN CROSSBREED CHICKENS FED PROBIOTIC BACILLUS BACTERIA: EVALUASI TOTAL BAKTERI DI USUS HALUS (ILEUM) PADA AYAM INDONESIA PERSILANGAN YANG DIBERI PAKAN MENGANDUNG PROBIOTIK BAKTERI BACILLUS - Aliya Inggita Prameswari (Journal Animal Research and Applied Science, 2022)
The purpose of this study was to determine the number of lactic acid bacteria, Coliform and Enterobacteria in the small intestine ileum of the Indonesian indigenous crossbreed chickens. The material used is 200 super unisex super native day old chick (DOC). The Indonesian indigenous crossbreed chickens received antibiotic and probiotic Bacillus treatment for 10 weeks mixed with rations. The research design that is proposed is a completely randomized design (CRD) consisting of 4 treatments with 5 replications, while the treatments applied are T0 (control), T1 (control + 0.04% Antibiotic (Zinc bacitracin)), T2 (control + 0, 01% commercial probiotics (Bacillus subtilis)) and T3 (control + 0.5% probiotics (Bacillus plus vitamins and minerals)). Parameters were taken randomly, 1 chicken from each experimental plot. The parameters observed were the total bacteria lactic acid, Coliform, and Enterobacter, The data were analyzed for their diversity at an accuracy of 5%. The results showed that there was no significant effect (P> 0.05) of treatment on the number of Coliform and Enterobacter bacteria, but a significant effect (P <0.05) on the increase in the number of lactic acid bacteria. It was concluded that giving Bacillus probiotics did not have an effect on the number of Coliform and Enterobacter bacteria but increased the number of lactic acid bacteria. Keywords : Coliform,  Enterobacteria, Ileum, Lactic acid bacteria